A79 Trauma survivors' decisions about using transport. Issue 2 (June 2015) - Braaf, Sandra; Gabbe, Belinda; Christie, Nicola; Cameron, Peter; Fitzgerald, Mark; Judson, Rodney; Harrison, James E; Lyons, Ronan A; Ponsford, Jennie; Collie, Alex; Ameratunga, Shanthi; Jowett, Helen; et al.
Abstract: Background: The impact of major trauma can pervade all aspects of an injured person's life. Many experience enduring changes in their transport routine, as ongoing disability is evident two years post injury. Little information is available about the considerations shaping, and consequences of, trauma survivors' selection and use of transport over the course of their recovery. This study aimed to explore the influences on trauma survivors' decisions about using transport and the outcomes of these decisions. Methods: This qualitative study draws on 90 semi-structured telephone interviews with major trauma patients three years after injury. The cohort for this study included major trauma patients, spinal cord injury patients, and patients and carers of patients with severe traumatic brain injury. All participants were recruited from the Victorian State Trauma Registry. Purposive sampling was used to ensure a balance of gender, Victorian Transport Accident Commission compensation status, region of residence, and definitive treatment administered at major and non-major trauma services. All interviews were audio recorded and transcribed. A thematic analysis was performed. Results: Key influences on trauma survivors' decisions about transport were logistical issues, physical state, attitudes and psychological considerations. Logistical issues included access to, reliability and availability of, appropriate transport, the cost of transport, weather conditions, distance to, and terrain at, the destination, familiarity with the travel path, and knowledge of transport options. Physical state considerations consisted of physical limitations, stage of recovery, level of pain and fatigue, the use of mobility aids, and the availability of assistance. Attitudes involved the perceived importance of the need to travel, concern about being judged on public transport, and worry about being a burden on others. Psychological considerations included the loss of self-confidence, feeling unsafe, holding a fear of driving and developing acute anxiety or panic attacks during travel. Three years after injury many patients had modified their mode of transport, reduced their use of public transport and endured extended travel times. Perceived and actual transport restrictions affected social interaction, employment opportunities, attendance at health care appointments and financial status. Pain and fatigue were reported with certain modes of transport, along with emotional distress and strained personal relationships, particularly with driving. Some sought psychological assistance to resume transport use. Conclusions: Insights into the decisions made by trauma survivors about using and selecting transport can inform the development of effective and timely interventions aimed to maximise independence and recovery.